1999
DOI: 10.1109/41.807990
|View full text |Cite
|
Sign up to set email alerts
|

A study on the discovery of relevant fuzzy rules using pseudobacterial genetic algorithm

Abstract: This paper presents a new method for the discovery of relevant fuzzy rules using the Pseudo-Bacterial Genetic Algorithm (PBGA). The PBGA was proposed by the authors as a new approach combining a genetic algorithm with a local improvement mechanism inspired by a process in bacterial genetics, named bacterial operation. The presented system aims the improvement of the quality of the generated fuzzy rules, producing blocks of e ective rules and more compact rule bases. This is achieved by encoding the fuzzy rules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Harvey [23] pointed out that gene interchange (as observed in bacteria [24,25]) could provide the rapid learning required. This was recently demonstrated by Furuhashi [26] for a bounded, globally optimised GA. In previous work [27] we have demonstrated that a novel unbounded, distributed GA with`b acterial learning'' is an eective adaptive control algorithm for the distribution of services in an active service provision system derived from the ALAN.…”
Section: Adaptive Controlmentioning
confidence: 73%
“…Harvey [23] pointed out that gene interchange (as observed in bacteria [24,25]) could provide the rapid learning required. This was recently demonstrated by Furuhashi [26] for a bounded, globally optimised GA. In previous work [27] we have demonstrated that a novel unbounded, distributed GA with`b acterial learning'' is an eective adaptive control algorithm for the distribution of services in an active service provision system derived from the ALAN.…”
Section: Adaptive Controlmentioning
confidence: 73%
“…Different authors present them as microbial genetic algorithms (Harvey, 1996), bacterial algorithms (Cabrita et al, 2003), pseudobacterial genetic algorithms (Nawa et al, 1999), lateral gene transfer (Ochman et al, 2000) and plasmid migration (Marshall and Roadknight, 2000) among others. In general, these algorithms avoid the sexual reproduction, so they are not classified as parallel genetic algorithms, although they are extremely distributed.…”
Section: Plasmid Migration and Bacterial Genetic Algorithmsmentioning
confidence: 98%
“…The randomly chosen ith part of the mÀ 1 clones is mutated and the best fitted part is replicated in the m individuals. After this mutationevaluation-selection-replacement process is repeated for all the p parts, the fittest individual goes to the next population and the other mÀ1 individuals die (Nawa et al, 1999;Cabrita et al, 2003).…”
Section: Plasmid Migration and Bacterial Genetic Algorithmsmentioning
confidence: 99%
“…Homaifar [10] used a GA to generate MFs and the rule-base simultaneously. Nawa and his co-workers [19] proposed a method for the discovery of relevant fuzzy rules using the pseudobacterial GA. However, in many of these methods the MFs partitions and the fuzzy labels are usually pre-deÿned and the rule base to be optimised becomes inevitably sizeable.…”
Section: Introductionmentioning
confidence: 99%